add 10 to left and right
-10+10-y=-3+10
-y=7
y=-7
2006-11-28 03:10:10
·
answer #1
·
answered by iyiogrenci 6
·
0⤊
0⤋
just take the -10 to the other side which makes it positive. so then you have -y=-3+10. -3 + 10 = 7. y=7, -y= -7.
2006-11-28 14:01:54
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
If you think of the = sign as the balance point of the expressions then the Left Hand Side is the same as the Right Hand Side
all you need do is keep adding the same quantities to both sides of the balance until you see a 'y' on one side and NO 'y'
on the other side.
so here we go.
add 'y' to both sides gives
-10 -y + y = -3 + y
(-y+y) =0 so LHS is simply -10
giving
-10 = -3 + y
Nearly there now.
add 3 to both sides to get rid if the -3 on the RHS
-10 + 3 = -3 + y + 3
(-10 + 3) is -7 and (-3 + 3) =0
so we get
-7 = +y
or y = -7
2006-11-28 11:17:31
·
answer #3
·
answered by deadbeat 1
·
0⤊
0⤋
-10 -y=-3
+10 +10
-y=7
y=-7
2006-11-28 11:17:12
·
answer #4
·
answered by deadgrl6 2
·
0⤊
0⤋
adding 10
-y=-3+10
-y=7
y=-7
2006-11-28 11:26:06
·
answer #5
·
answered by raj 7
·
0⤊
0⤋
add 10 to both sides
-y = 7
divide by -1
y = -7
2006-11-28 11:28:03
·
answer #6
·
answered by unan1m0us 5
·
0⤊
0⤋
-10-y =-3
-y = -3+10
-y = 7
so y = -7 Ans.
2006-11-28 11:15:48
·
answer #7
·
answered by aminnyus 2
·
0⤊
0⤋
add 10 to both sides of the equation. -y = 7, multiply both sides by -1
y = -7
Since your question stated that the coeficient of y be positive that's why you multiply by -1, other wise -y = 7 would be the answer.
2006-11-28 11:33:20
·
answer #8
·
answered by ikeman32 6
·
0⤊
0⤋
-7
2006-11-28 11:14:28
·
answer #9
·
answered by Joseph C 1
·
0⤊
0⤋
-7
2006-11-28 11:10:05
·
answer #10
·
answered by fm02 2
·
0⤊
0⤋